Creating Customer Loyalty Based on Brand Image, Service Quality, Learning Quality, by Mediation of Customer Trust in Purwacaraka Music Studio - Ayu Nareswari; Nawangsih Nawangsih; Rendra Wirawan (Innovation Business Management and Accounting Journal, 2023)
The purpose of this research is to understand what contributes to customer loyalty, such as brand image, quality of service, and quality of learning. The analytical method to be used in this study is quantitative analysis using the Smart PLS (Partial Least Squares) method. The Smart PLS method is an appropriate method for examining the relationship between complex construct variables and for understanding the mediating effect between these variables. We will analyze the relationship between brand image, service quality, learning quality, customer trust and customer loyalty at Purwa Caraka Music Studio using data collected through a survey of active customers. The sample used was 200 people. The results showed that customer trust proved to play a mediating role in creating customer loyalty based on brand image, service quality, and learning quality. However, these results have not been explored further in the past, and can be used as a performance evaluation for other Purwa Caraka Music Studio Branches and studies for future marketing strategy programs.